Japanese Language Proficiency Among Malaysian Japanese Speaking Graduate Employees: A Study In Japanese Companies In Malaysia - Yeoh, Lee Su (2018)
The main purpose of this mixed methods study was to investigate Japanese language skills‘ proficiency among Malaysian Japanese Speaking Graduate Employees (MJSGEs) in Japanese Companies in Malaysia (JCM). Specifically, the requirements and level of importance of Japanese language proficiency in listening, speaking, reading, and writing among MJSGEs were examined. This study also investigated the challenges faced by MJSGEs in using the Japanese language in JCM and the measures they adopted to overcome these challenges. Both quantitative and qualitative data were collected. A questionnaire was used to collect quantitative data from 65 respondents. Qualitative data were collected by employing semi-structured interviews with 17 MJSGEs and eight (8) Japanese employers in JCM. While the quantitative data were analysed using the Statistical Package for the Social Sciences (SPSS), the qualitative data were transcribed and analysed thematically. The results revealed that the Japanese language skills‘ proficiency requirements considered important by employers in JCM in the workplace were the listening skills (understanding oral instructions and the ability to confirm information) and speaking skills (work-related and daily communication with Japanese colleagues). The findings indicate that listening and speaking skills were ranked more highly than reading and writing which is ranked the lowest. Listening and speaking were also the most challenging skills faced by MJSGEs. To overcome the challenges, MJSGEs employed certain measures including getting guidance from the internal workplace community such as their Japanese colleagues and superiors and the external measure of utilising internet sources. MJSGEs are found to be intrinsically motivated to solve all their Japanese language skills-related issues. The findings of this study can support the setting-up of a Business Japanese major programme for Malaysian higher education institutions. In such a manner, this study become more significant.